(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Ultrasound is very useful for the study of appendicitis and its diagnostic approach because it is easily available and harmless, which makes it the main technique or method of choice in the imaging study of all appendicitis in children